PENGARUH PRICE DAN SERVICE QUALITY TERHADAP CUSTOMER LOYALTYPADA BLACK DEW CAFE PACET MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Fitri Dhea Lusanti; Mei Indrawati; Indra Prasetyo (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study is based on the phenomenon that occurs where customer loyalty problems faced by Black Dew Café Pacet are in the midst of variations in customer perception of price and service quality. The problem in this study is "Does Price and Service Quality Affect Customer Loyalty through Customer Satisfaction at Black Dew Café Pacet". In this study, data was collected with a questionnaire distributed to 150 respondents as customersof Black Dew Café Pacet. Data analysis was conducted using SEM-PLS supported by SmartPLS 3.0 software. The findings of the study show that: (1) Price has a real impact on Customer Satisfaction; (2) The quality of service has no real impact on customer Satisfaction; (3) Price doesnot directly have a significant influence on Customer Loyalty; (4) Service Quality directly has a real influence on Customer Loyalty; (5) Customer Satisfaction has a real influence on Customer Loyalty; (6) Price has a real impact on Customer Loyalty through Customer Satisfaction; and (7) Service Quality has no significant impact on Customer Loyalty through Customer Satisfaction.